A Raman investigation of the structural evolution of supercooled liquid barium disilicate during crystallization. (8th June 2018) - Moulton, Benjamin J. A.; Rodrigues, Alisson Mendes; Pizani, Paulo Sergio; Sampaio, David Vieira; Zanotto, Edgar Dutra
Abstract: The homogeneous and stoichiometric crystallization of the barium disilicate (BaSi2 O5 ) glass makes it possible to follow the structural evolution of Raman bands from the supercooled liquid to the crystalline phase. We monitored the crystallization of supercooled liquid BaSi2 O5 at 790°C over 440 minutes revealing a three‐stage crystallization process: stage 1 involves changes in the barium sites toward a bonding environment that is similar to that in orthorhombic low barium disilicate. The end of stage 1 is marked by the loss of the Q 4 species vibration at 1170 cm −1 and the creation of a crystalline band at 490 cm −1 . Stage 2 is marked by the transition of the Q 3 peak (1060 cm −1 ) from a Gaussian‐like to a Lorentzian curve, indicating the formation of well‐developed sheet structures. These observations lead us to conclude that the Raman spectra are resolving both the crystalline L‐BS2 phase and the BS2 melt. The final stage involves a rapid decrease in the remaining Q n species to form Q 3 . This crystallization process involves structural modifications that occur on the tens of microns scale. The barium cations drive the initial stages of crystallization, providing direct evidence that the short‐range order, around network modifiers, is a critical factor involved in homogeneous crystallization.